The technological transformation of higher education in the context of the COVID-19 pandemic – Knowledge and challenges - Souza, Ana Beatriz Carvalho de; Amaral, Augusto Minelli; Oliveira, Bianca Andriguetto; Salomão, Eduarda Tsuneme Hayashi; Barbosa, Barbara (Seven Editora, 2023)
In 2020 the first cases of COVID-19 were diagnosed in Brazil. A worldwide virus that caused a pandemic and a quarantine was established in much of the world, a way to avoid personal contact in order to control the spread. It has the objective of showing the adaptations, methods and feelings of the students and teachers adopted in this pandemic, with an integrative study methodology and virtual research, based on the last 5 years. Twenty-four articles were discussed, resulting in the adaptation of the new routine with digital platforms and interactions through video-classes, animations, among others. It was reported that the lack of a stable connection and modern devices hindered the interaction in these online classes proposed by the universities. It is possible to conclude that despite the difficulty with the adaptations, creating an educational and practical way to present the classes, with the application of assessments and interactions by various means, made that education did not suspend. DOI:https://doi.org/10.56238/sevened2023.004-045